2016
DOI: 10.3389/fpls.2016.00042
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a 467 bp Promoter of Maize Phosphatidylinositol Synthase Gene (ZmPIS) Which Confers High-Level Gene Expression and Salinity or Osmotic Stress Inducibility in Transgenic Tobacco

Abstract: Salinity and drought often affect plant growth and crop yields. Cloning and identification of salinity and drought stress inducible promoters is of great significance for their use in the genetic improvement of crop resistance. Previous studies showed that phosphatidylinositol synthase is involved in plant salinity and drought stress responses but its promoter has not been characterized by far. In the study, the promoter (pZmPIS, 1834 bp upstream region of the translation initiation site) was isolated from mai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 54 publications
0
20
0
Order By: Relevance
“…We have found the ABRE which is acis-acting element of abscisic acid (ABA). The studies have reported that ABA is an important plant hormone involved in many important biological processes and reactions, including abiotic stresses [41,42], so we speculate that MADS3 may regulate the expression of this gene by binding to the ABRE element on the MaPIP1;1 promoter. Or maybe the M-P2 region may contain as yet unknown cis-acting elements that are critical for MaPIP1;1-mediated responses to drought stress.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…We have found the ABRE which is acis-acting element of abscisic acid (ABA). The studies have reported that ABA is an important plant hormone involved in many important biological processes and reactions, including abiotic stresses [41,42], so we speculate that MADS3 may regulate the expression of this gene by binding to the ABRE element on the MaPIP1;1 promoter. Or maybe the M-P2 region may contain as yet unknown cis-acting elements that are critical for MaPIP1;1-mediated responses to drought stress.…”
Section: Discussionmentioning
confidence: 90%
“…Genetic modifications that target genes and their promoters can be used to enhance crop performance [43]. However, overexpression of transgenes can hamper plant growth and development, by imparting inefficient energy metabolism or morphological and/or physiological dysfunction [27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43]. Thus, inducible promoters that selectively drive expression of target genes under specific environmental conditions can be used to avoid negative effects of excess expression that can occur with the use of constitutive promoters [44][45][46][47].…”
Section: Discussionmentioning
confidence: 99%
“…Promoters play important roles in initiating gene transcription and regulating the expression of transgenes. Therefore, a good knowledge of promoter transcriptional activities and expression patterns is necessary for the successful application of transgenic breeding and gene function studies [ 5 , 53 ]. In this study, the AtSCPL30 promoter from Arabidopsis thaliana was isolated and characterized by deletion analysis in Nicotiana benthamiana transgenic plants.…”
Section: Discussionmentioning
confidence: 99%
“…The major challenges in the successful application of transgenic technology are the precise control of transgenes or endogenous gene expression [ 2 ]. Appropriate promoters are crucial for the regulation of the transgenes expression at desired profile, thereby promoting the successful application of transgenic technology, while the number and type of promoters for plant genetic transformation are still quite limited [ 2 5 ]. Therefore, cloning and characterization of various promoters suitable for plant genetic transformation is highly desirable [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation